O basquetebol em números : análise de indicadores de jogo do NBB 2018-2019 - Canan, Felipe; Malagutti, João Paulo Melleiro; Hirata, Edson (2021)
The objective of this work was to identify the most important game indicators for victory in a match and to define the final placement in the classification phase of the 2018-2019 season of the New Basketball Brazil (Novo Basquete Brasil, in Portuguese). The research is quantitative-descriptive and analyzes 43 direct (box score) and indirect game indicators (advanced statistics and four factors), in addition to the partial score of the 179 games available on the National Basketball League (Liga Nacional de Basquete, in Portuguese) website. Total and average values,quantities and percentages of times were calculated when the winner or loser of each match was superior in each indicator and in which the first and last place of the competition classification phase were superior as well in each indicator. It was identified that indicators related to the quantity and percentage of correct pitches in general are preponderant for victory in each match and to end up first in the classification phase. Rebounds are more important for victory in each match than for first place in qualifying. In general terms, winning teams are more careful with the ball and have better selection of shots.
Objetivou-se identificar os indicadores de jogo mais importantes para vitória em uma partida e para a definição da colocação final na fase de classificação da temporada 2018-2019 do Novo Basquete Brasil. A pesquisa é quantitativa-descritiva e analisou 43 indicadores diretos (box score) e indiretos de jogo (estatísticas avançadas e four factors), além da pontuação parcial das 179 partidas disponibilizadas no site da LNB. Computou-se valores totais e médias e quantidades e percentuais de vezes em que o vencedor ou perdedor de cada partida foi superior em cada indicador e em que o primeiro e o último colocado da fase de classificação da competição foram superiores em cada indicador. Identificou-se que indicadores relacionados à quantidade e percentual de acerto de arremesso em geral são preponderantes para vitória em cada partida e para terminar em primeiro lugar na fase de classificação. Rebotes são mais importantes para vitória em cada partida do que para primeira colocação na fase de classificação. Em termos gerais, equipes vitoriosas têm mais cuidado com a bola e melhor seleção de arremessos.
Keywords: Sport; Basketball; NBB; Esporte^lpt; Basquetebol; NBB